Effectiveness of Learning at State Vocational School 4 Takalar - Haerati Haerati; Risma Niswaty; Nasaruddin Hasyim (ASHA Publishing, 2025)
This research is motivated by the importance of learning effectiveness in improving the quality of optimal education, especially in Vocational High Schools (SMK), which emphasize practice-based and skills-based learning. The purpose of this study was to evaluate the effectiveness of learning at SMK Negeri 4 Takalar and to identify the supporting and inhibiting factors. This study used a qualitative approach with data collection through observation, interviews, and documentation. The results showed that the effectiveness of learning at SMK Negeri 4 Takalar was classified as